Rapid Onset of B12 Deficiency in the Setting of Worsening Multiple Myeloma: Correlations between B12 Deficiency and Multiple Myeloma. (31st July 2017) - Seegobin, Karan; Maharaj, Satish; Nelson, Grant; Carlson, Jeremy; Baldeo, Cherisse; Jacob, Rafik
Abstract : A 67-year-old female with a relapse of multiple myeloma after being in remission for approximately 2 years following autologous stem cell transplant presented with worsening pancytopenia, over a three-month period. There were an increase in her monoclonal spike at 3.13 g/dL on serum protein electrophoresis, low serum B12 levels, and positive intrinsic factor antibodies. Three months before, she had normal B12 levels and a significantly lower monoclonal spike of 1.07 g/dL. She was diagnosed with B12 deficiency with pernicious anaemia in the setting of her worsening myeloma. Multiple myeloma (MM) has been linked with B12 deficiency and pernicious anaemia. Several mechanisms have been described regarding the pathogenesis of B12 deficiency in such patients. Increased tumour activity can further perpetuate the development of B12 deficiency in such patients. With regard to our case, the increase in tumour activity and onset of pernicious anaemia could have contributed to the rapid development of B12 deficiency. In contrast to this, rapid development of B12 deficiency could also signify relapse or worsening of the myeloma as seen in our case. Physicians ought to consider B12 deficiency in patients with worsening pancytopenia and myeloma.